1990
DOI: 10.3109/00016349009013305
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Oral Fluconazole Versus Single‐Dose Topical Miconazole for the Treatment of Acute Vulvovaginal Candidosis

Abstract: A single dose fluconazole is as safe and effective as a single dose of miconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…They are as effective as intravaginal treatment of vulvovaginal candidiasis, but gastrointestinal toxicity resulting in nausea, vomiting, and diarrhea is common, occurring in up to 15% of patients. 45,46 One-dose topical treatments are also available (tioconazole 6.5% vaginal ointment, clotrimazole 500-mg vaginal suppository), but appear to have less efficacy than other preparations. 47 For patients with frequently recurrent candidal vaginitis, it is important to consider factors that predispose to infection.…”
Section: Treatmentmentioning
confidence: 99%
“…They are as effective as intravaginal treatment of vulvovaginal candidiasis, but gastrointestinal toxicity resulting in nausea, vomiting, and diarrhea is common, occurring in up to 15% of patients. 45,46 One-dose topical treatments are also available (tioconazole 6.5% vaginal ointment, clotrimazole 500-mg vaginal suppository), but appear to have less efficacy than other preparations. 47 For patients with frequently recurrent candidal vaginitis, it is important to consider factors that predispose to infection.…”
Section: Treatmentmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention recommend two doses of oral fluconazole 150 mg to treat SVVC [3]. Several studies have demonstrated that uncomplicated VVC responds well to a single dose of miconazole nitrate vaginal suppository 1,200 mg [4,5,6,7,8,9]. The effect of miconazole nitrate vaginal suppository 1,200 mg on SVVC is not known.…”
Section: Introductionmentioning
confidence: 99%
“…From the clinical point of view, the study incorporates some new aspects to measure therapeutic response. In most drug-efficacy studies, clinical cure is assessed after 7 days [ 12 , 17 , 18 , 20 ], and after 5-16 days [ 11 , 35 , 36 ] but we think it is interesting to evaluate the time for the relief of symptoms, since there is disagreement about whether the symptoms were relieved earlier with oral or topical drugs. In this way, Seidman LS [ 37 ] reported that the relief of symptoms is 24 hours with topics and 46 hours with orals.…”
Section: Discussionmentioning
confidence: 99%
“…Ten clinical trials dealt with women's preference regarding the anti-fungals way of administration, but the presented data were not sufficient to answer this question [ 10 - 20 ]. The Cochrane review's authors concluded that all studies that dealt with preferences are in favor of oral treatment (compared to intravaginal or no preference) with a fluctuation from 43% for women at Van Heusdenal's trial [ 20 ] to 93% at Timonen's trial [ 16 ]. Nevertheless, inconsistencies associated with the report of the preferred way of administration limit the use of such data.…”
Section: Introductionmentioning
confidence: 99%